The reliability of repeated TMS measures in older adults and in patients with subacute and chronic stroke - Schambra, Heidi M.; Ogden, R. Todd; Martínez-Hernández, Isis; Lin, Xuejing; Chang, Y. Brenda; Rahman, Asif; Edwards, Dylan; Krakauer, John W. (Frontiers in Cellular Neuroscience, 2015)
The reliability of transcranial magnetic stimulation (TMS) measures in healthy older adults and stroke patients has been insufficiently characterized. We determined whether common TMS measures could reliably evaluate change in individuals and in groups using the smallest detectable change (SDC), or could tell subjects apart using the intraclass correlation coefficient (ICC). We used a single-rater test-retest design in older healthy, subacute stroke, and chronic stroke subjects. At twice daily sessions on two consecutive days, we recorded resting motor threshold, test stimulus intensity, recruitment curves, short-interval intracortical inhibition and facilitation, and long-interval intracortical inhibition. Using variances estimated from a random effects model, we calculated the SDC and ICC for each TMS measure. For all TMS measures in all groups, SDCs for single subjects were large; only with modest group sizes did the SDCs become low. Thus, while these TMS measures cannot be reliably used as a biomarker to detect individual change, they can reliably detect change exceeding measurement noise in moderate-sized groups. For several of the TMS measures, ICCs were universally high, suggesting that they can reliably discriminate between subjects. Though most TMS measures have sufficient reliability in particular contexts, work establishing their validity, responsiveness, and clinical relevance is still needed.